Attributes of Polymer and Silica Nanoparticle Composites: A Review. (23rd May 2016) - Meer, Sanaa; Kausar, Ayesha; Iqbal, Tahir
ABSTRACT: In this article, polymer microspheres and silica nanoparticles have been discussed as important filler in polymer composites. Their synthesis methods, properties, and application were particularly stressed. Silica is usually used as nucleating agent, surface enhancement mediator, and as templates and cores. Among polymer/silica composites, various categories including polyaniline, polypyrrole, polystyrene, epoxy, rubber, and acrylate polymer were discussed in detail. It was observed that silica nanoparticles enhanced mechanical strength and overall performance of composites. Furthermore, composites having carbon nanotube along with silica particles possess high electrical and mechanical performance. These composites are important in nanoelectronic devices, nanomedicines, and defense-related applications. GRAPHICAL ABSTRACT: